Effects on the development of Spodoptera frugiperda feeding on diets spiked with Solanum sisymbriifolium extracts - Migues, Ignacio; de Barros, Neiva Montero; Rech, Vânia; Dutra, Carmelo; Díaz, Alejandro Ruiz; Malaquias, Juaci Vitória; Specht, Alexandre; Heinzen, Horacio; Cesio, Maria Veronica (Eclética Química, 2020)
Aiming to evaluate the effects of Solanum sisymbriifolium extracts on the development of Spodoptera frugiperda, a leaf dichloromethane extract was obtained and subjected to further purification following a bioguided methodology. The structure of the two main compounds isolated from S. sisymbriifolium Type IV glandular trichomes have been completely elucidated by a combination of chemical and spectroscopic methods. They are glycosides of 3-(R)-hydroxypalmitic acid and xylo (β-1-5) furanoarabinoside (Compound 1) and its 3-O-palmitoyl derivative (Compound 2). These compounds greatly influenced the survival and the development of S. frugiperda, when compared to an in vitro test control. The extracts delayed the development, decreased survival and promote abnormalities in the immatures (larvae and pupae). They also showed increasing toxicity towards S. frugiperda in the purification following a bioguided fractionation. The pure compounds had the most deleterious activity, increasing the larval and pupal toxicity (100% mortality for Compound 2 at 2.50 mg mL-1 and 90% mortality for Compound 1 at 1.00 mg mL-1).